PROSPEK PENGEMBANGAN PERKEBUNAN KARET (Hevea brasiliensis) RAKYAT DI DESA MARGAHAYU KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Rita Mariati; Tetty Wijayanti; Heru Marsa'id (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2020)
Rubber plants are one of the important plantation commodities in Kutai Kartanegara Regency, both as a source of income, employment opportunities and driving new economic centersin East Kalimantan. However,the low productivity of rubber plants caused many rubber farmers to switch to other sectors. The purpose of this study is to identify internal and external factors, as well analyzing the prospect of developing rubber farming in Margahayu Village.Research has been carried out from July to August 2018 in Margahayu Village, Loa Kulu District, Kutai Kartanegara District. The research method used was surveys and interviews. The location was determined by purposive sampling. Data collected in this study are primary and secondary data. Data collection method is done by observation, direct interviews with respondents and library studies. Data were analyzed using SWOT analysis.The results showed that the most appropriate alternative was the SO strategy (Strength and Opportunity), because the strategy had the highest score of 4.32. The development of rubber farming in Margahayu Village can be done with the following alternative strategies: The use of superior clone seeds to increase the productivity of rubber crops, establish cooperation with the government or the private sector for the development of rubber plantations, strengthen the information system among members of farmer groups.